Moment tests of independent components - Dante Amengual; Gabriele Fiorentini; Enrique Sentana (SERIEs - Journal of the Spanish Economic Association, 2022)
We propose simple specification tests for independent component analysis and structural vector autoregressions with non-Gaussian shocks that check the normality of a single shock and the potential cross-sectional dependence among several of them. Our tests compare the integer (product) moments of the shocks in the sample with their population counterparts. Importantly, we explicitly consider the sampling variability resulting from using shocks computed with consistent parameter estimators. We study the finite sample size of our tests in several simulation exercises and discuss some bootstrap procedures. We also show that our tests have non-negligible power against a variety of empirically plausible alternatives.
Keywords: C32; C46; C52; 330; Co-kurtosis; Co-skewness; Covariance; Finite normal mixtures; Normality tests; Pseudo-maximum likelihood estimators; Structural vector autoregressions